The Relationship Between Nurses' Knowledge And Skills In Carrying Out Mucus Suction In The Intensive Care Unit (ICU) Room Of Haji Hospital Medan In 2023 - Idris, Syamsul (Jurnal EduHealth, 2024)
The act of suctioning is an action that is often performed by nurses to avoid complications from the act of suctioning, nurses must perform suctioning actions according to the procedure of the procedure. Related factors include nurse knowledge, action skills. This study aims to determine the relationship between Nurses' Knowledge and skills in performing suction in the Intensive Care Unit (ICU) Room of the North Sumatra Hajj Hospital in 2023. This type of research is a quantitative research with a descriptive method of correlation with cross sectional. The population in this study is 20 nurses in the ICU Room. Sampling was done using the Total Sampling technique. The data collection method uses questionnaires and observations. The statistical test used in this study is chi square with a confidence level of 95% (α=0.5). The results of the study based on chi square obtained a p-value of 0.003<0.05, the majority of nurses' knowledge in carrying out suction in the Intensive Care Unit (ICU) Room of Haji Hospital in 2023 was high, and the skills of nurses in carrying out suction in the Intensive Care Unit (ICU) Room of Haji Hospital Medan in 2023. The conclusion of the study showed that there was a relationship between Nurses' Knowledge and skills in Performing Mucus Suction in the Intensive Care Unit (ICU) Room of Haji Hospital Medan in 2023. So it is hoped that the Hospital will provide training to nurses in the act of sucking mucus (Suction) and carried out in accordance with SOPs.